The impact of the use of focused reading strategies for the improvement of A2 level english students’ reading comprehension-performance at the Foreign Language Department of the University of El Salvador. - Flores Acosta, Maritza Elizabeth; López de Meléndez, Dora Lilian; Pérez López, Cledis Sugeidy; Contreras Cárcamo, Mauricio Salvador; Landaverde Castillo, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2016)
The results of this type of research are expected to be useful and relevant to the researchers, the professors, the students and the co-workers. Critical reflection is the most important aspect of qualitative and quantitative research. Giving priority to qualitative data, which can provide to the foreign language educational field a significant information about the impact of focused reading strategies in the improvement of reading comprehension performance? The goal of this research is to find out the impact of focused reading strategies in the improvement of A2 level English intermediate I students‟ reading comprehension performance and help learners to start coping with the difficulties that many students have when facing reading exercises and exams in the foreign language classroom and when reading for pleasure in their everyday lives. For this research, we will take into account the information proposed by The Common European Framework of Reference for Languages: Learning, Teaching, Assessment (regarding the reading proficiency levels according to the CEFRL 2001, see annex 1) about reading comprehension of written texts and a number of strategies that can help students to overcome difficulties when developing this skill. In the first chapter, we will expose the interest of this research. We will present the sample of students this research was based upon. In the second chapter, we begin with a theoretical justification. The third chapter presents the methodology which reports the experienced events during the implementation of a wide number of sensitive and focused reception strategies that can help overcome the problems that students face when working on a reading intensively or extensively inside and outside the classroom. Then, we will present the analysis of the quantitative and qualitative data in chapter four. Finally, in chapter five, we will expose our conclusions and recommendations as a result of this research.
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2016
Bibliografía : 77-78
Audiencia general.
Keywords: Intensive and extensive reading; Sensitive and focused reception reading strategies